A low-molecular-weight heparin-coated doxorubicin-liposome for the prevention of melanoma metastasis. (May 2015) - Chen, Yi; Peng, Jianqing; Han, Miaomiao; Omar, Mezghrani; Hu, Danrong; Ke, Xue; Lu, Na
Abstract Tumor metastasis is the biggest challenge in cancer therapy. During the metastasis process, metastatic cells could acquire stealth ability toward immune system through the formation of a protection cloak by hijacking platelets (PTs). Heparins, a heterogeneous mixture of glycosaminoglycans, can inhibit metastatic cascades by blocking P-selectin-mediated intercellular adhesion between tumor cells and PTs. In this study, low-molecular-weight heparin-coated doxorubicin-loaded liposome (LMWH-DOX-Lip) was developed for metastasis preventative therapy. The formation of LMWH-DOX-Lip was based on electrostatic interactions between the negatively charged heparins and cationic lipids. LMWH-DOX-Lip prepared at the optimum prescription possessed high entrapment efficiency, ideal particle size and zeta potential. Morphology of LMWH-DOX-Lip was characterized by atomic force microscopy and transmission electron microscopy. The results of confocal microscopic observations and flow cytometry analysis indicated that LMWH-DOX-Lip mediated an efficient cellular uptake in B16F10 melanoma cell line. Besides, LMWH-DOX-Lip displayed an increased cytotoxic over their unmodified counterparts. Furthermore, the inhibition effect of LMWH-DOX-Lip on adhesion between tumor cells and PTs/P-selectin was observed. In vivo study performed on a pulmonary melanoma mouse model revealed a substantially tumor metastasis prevention by LMWH-DOX-Lip. All these results suggested that LMWH-DOX-Lip could significantly inhibit metastasis through preventing the tumor cell–platelet interactions and in the meantime suppressed tumor growth.